Hindu Initiation and Death Rituals: A Jungian Perspective on Individuation - Poudel, Jeevan (NPRC Journal of Multidisciplinary Research, 2025)
This paper explores Hindu initiation and death rituals through the lens of Jungian individuation theory, identifying their psychological and transformative relevance beyond religious practices. Individuation, in Jungian psychology, refers to the process by which an individual integrates various aspects of the psyche both conscious and unconscious to achieve a unified and authentic self. The Upanayana ceremony, which traditionally marks a young boy's transition into disciplined learning and spiritual responsibility, represents the beginning of individuation by facilitating detachment from familial and societal bonds, removing egoic attachments, and cultivating self-awareness. Similarly, Hindu death rites function as significant psychological processes that help the performer through mourning, introspection, and the integration of conscious and unconscious identities. These rites allow people to confront death, learn detachment, and harmonize with the cosmic order. A critical re-examination of gender roles within these rituals indicates that, whereas men participate in symbolic rites to initiate individuation, women do so more directly through biological and social events such as menstruation, childbirth, and care-giving. This viewpoint challenges traditional critiques of exclusivity and maintains that individuation is a universal but gender-specific journey. The study employs a theoretical and symbolic analysis rooted in classical Hindu texts and Jungian psychological concepts. Itemphasizes the decline in enthusiasm for ritual acts, claiming a lack of symbolic comprehension. By reframing rituals as processes for personal growth and self-discovery, they might be revived to fulfill modern psychological and spiritual requirements. Finally, this study emphasizes Hindu ritual's lasting importance, establishing them as bridges between tradition and transformation while reinforcing their role in creating self-awareness, purpose, and collective well-being.